2021
DOI: 10.1186/s12967-021-02825-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting lactate dehydrogenase a improves radiotherapy efficacy in non-small cell lung cancer: from bedside to bench

Abstract: Background Lactate dehydrogenase A (LDHA) is overexpressed and associated with poor prognosis in many kinds of cancer. In the current study, we evaluated the prognostic value of LDHA expression in non-small cell lung cancer (NSCLC), and tested whether LDHA inhibition might improve radiotherapy efficacy in NSCLC. Methods LDHA expression was investigated in NSCLC patients, using online database and further verified by immunohistochemistry. The progno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 59 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…Our previous study [26] has revealed that oxamate, an inhibitor of LDH-A, signi cantly suppressed the proliferation of NSCLC cells, while it exerted a much lower toxicity in normal cells. LDH-A inhibition resulted in ATP reduction and ROS (reactive oxygen species) burst in cancer cells, which lead to apoptosis and G2/M arrest and increase radiosensitivity in NSCLC cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study [26] has revealed that oxamate, an inhibitor of LDH-A, signi cantly suppressed the proliferation of NSCLC cells, while it exerted a much lower toxicity in normal cells. LDH-A inhibition resulted in ATP reduction and ROS (reactive oxygen species) burst in cancer cells, which lead to apoptosis and G2/M arrest and increase radiosensitivity in NSCLC cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…The analyses of LDHA and PDK1 in situ protein expression also showed association with poor survival and therapy resistance in many malignancies (colon, breast, uterine, pancreas, lung, renal, gastric cancers, CNS malignancies, etc.). Considering the increasing serum lactate level of end-stage cachexia patients, these observations are not surprising [196][197][198][199][200][201].…”
Section: Tissue Heterogeneity Of Certain Metabolic Enzymes and Their ...mentioning
confidence: 83%
“…The overexpression of the metabolic enzyme LDHA is necessary for tumor growth and progression (6)(7)(8)(9)(10)(13)(14)(15). LDHA typically exists as a tetramer (LDH-5) and functions primarily to interconvert pyruvate to lactate and transform NADH to NAD+.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a number of enzymes and transporters that promote glycolysis and glucose metabolism are overexpressed in cancer cells relative to normal cells (4,5). One such enzyme, lactic acid dehydrogenase A (LDHA), is known to be overexpressed in several cancer types and associated with poor prognosis (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%